Does Democracy Have A Future? Selected Cases From Southeast Asia - Linda, Alfarero Lumayag (UNIMAS Publisher, 2023)
This book is a compilation of selected papers at the Third International Conference on Elections and Democracy (E&D) on April 19-20 2017, in Kuching Sarawak which carried the theme "Does Democracy Have a Future?'. This meeting of academics, policy makers and political thinkers in Southeast Asia is one of the flagship conferences under the auspices of the Faculty of Social Sciences and Humanities at Universiti Malaysia Sarawak (UNIMAS).